Religious Digital Literacy of Islamic Education Students ‎at Indonesia State Islamic University - Bobi Erno Rusadi; Syamsul Aripin (TADRIS: Jurnal Pendidikan Islam, 2023)
Nowadays, most campuses use the internet for their learning process. Students may search the Internet for literature or information related to the lectures. This phenomenon has an impact on students' behavior in studying religion through the Internet. This phenomenon raises worries because not a few students surf in cyberspace and try to look for information related to religious issues without any further explanation. Furthermore, they did not check the validity of the information. This paper aims to describe and analyze students’ ability in religious digital literacy. The sources come from Islamic religious students at some State Islamic University under the Ministry of Religious Affairs. This is mix-method research with explanatory sequential. In collecting data, the researcher used questionnaires and interviews. Data analysis techniques were performed with descriptive quantitative analysis and qualitative analysis. This research shows that from eight components of digital literacy, including components of functional skills and beyond ability students of Islamic religious education in the "excellent" category, the component of creativity in the "good" category, components of collaboration in the "good" category, components effective communication in the "good" category, components the ability to find and select information in the "good" category, components of critical thinking and evaluation in the "good" category, components of cultural and social understanding in the "good" category, and components e-safety in "good" category. The kindly whole from every component from such digital literacy, then religious digital literacy of students of Islamic religious education is at an interval value of 4.0 who enter in the "good" category.